ANALYSIS OF FACTORS INFLUENCING COMPLIANCE WITH THE USE OF PERSONAL PROTECTIVE EQUIPMENT BY PT JMKT FIELD WORKERS - Tri Niswati Utami; Junaisa Intan Farashati; Selvia Ramadani; Azzahra Chandra Syafira; Nadia Rizka Yulianda; Muhammad Iqbal Haqiqi Zein; Abdul Hadi Junaidi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Compliance in the use of Personal Protective Equipment (PPE) is an important element in the implementation of the Occupational Safety and Health (K3) system. “However, in reality, the level of worker compliance in the field is still relatively low, especially in the area of toll road management and maintenance. This study aims to identify and analyze the factors that influence the compliance of PT Jasamarga Kualanamu Tol field workers in the use of PPE during work. The study used a quantitative approach with a cross-sectional analytical observational design. A total of 30 field workers were selected as respondents using a total sampling technique. Data were collected through questionnaires, direct observation, and interviews, then analyzed using the Chi-Square test with a significance level of p < 0.05. The results showed a significant relationship between the level of knowledge (p = 0.025) and attitude (p = 0.035) with compliance in the use of PPE. In contrast, the variables of PPE availability (p = 0.098) and supervision (p = 0.113) did not have a significant relationship with the level of worker compliance. Worker knowledge and attitudes play an important role in encouraging compliance in the use of PPE, while the availability and supervision factors have not been proven to have a significant influence. Therefore, efforts are needed to increase ongoing socialization and training of K3, strengthen safety culture in the work environment, and implementation of more effective monitoring mechanisms to foster safe work behavior among field workers.